La influencia de la orientación vocacional en la autoestima de estudiantes de décimo año en la unidad educativa Nicolás infante Díaz - Sanchez Cedeño, Betsi Cecilia (2025)
Career guidance is a significant process in the personal and academic development of all students. The overall objective of this research is to analyze the influence of career guidance on the self-esteem of tenth-year upper elementary students at the Nicolás Infante Díaz School. The results indicate that the majority of students (63%) are undecided about their major, suggesting a need for greater support in academic decision-making. Regarding career guidance activities, 38% of respondents experienced significant reflection, although 23% also reported negative experiences. Regarding skill development, 42% discovered new abilities, while 30% changed their self-esteem. The students showed diverse reactions to challenges, with 25% expressing confidence and 25% expressing frustration. When evaluating self-confidence, 42% rated the guidance experience as extraordinary, although 23% expressed low confidence. The influence of career guidance on confidence was positive for 37% of students, although some reported little influence. Finally, most students feel more confident in their academic choices, although doubts and a lack of clarity remain, highlighting the need to improve career guidance strategies to foster greater self-confidence and clarity in their decisions.